PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS NASABAH PT. BANK MANDIRI (PERSERO) Tbk, KC DOTULOLONG LASUT MANADO - DAHLAN, PUTRI WINDARWATI M.; Tampi, Johny R. E.; Tumbel, Tinneke M. (JURNAL ADMINISTRASI BISNIS, 2017)
This study aims to determine the influence of Customer Relationship Management on customer loyalty in PT. Bank Mandiri (Persero) Tbk, KC Dotulolong Lasut Manado. This research is quantitive research using survey method. Data collection technique is done by division of questionnaires filled by 100 respondents who become the sample in this research. Data collection was done with questionnaires that have been tested for validity and reliability. Data analysis use is descriptive statistic, consisting of correlation coefficient and simple regression done by using program SPSS. The result of the research shows that there is significant influence between Customer Relationship Management on customer loyalty. Customer Relationship Management is a very important thing for the company to establish long-term relationships with customers in order to achieve satisfaction that also impact on customer loyalty, then for the benefit of the two parties, the company further improve and optimize the system Customer Relationship Management to increase customer loyalty. Keyword: Customer Relationship Management, customer loyalty.